ANALISIS PENGARUH EKUITAS MEREK DIGITAL TERHADAP KEPUTUSAN PEMBELIAN KOPI MENAKAR YOGYAKARTA - Oryz Agnu Dian Wulandari, Oryz Agnu Dian Wulandari; Dhea Praadha Gitama, Gytha Nurhana; Kart, Ika (Jurnal Witana, 2024)
This study aims to analyze the influence of several factors on consumer purchase decisions for Kopi Menakar products. The factors analyzed include Service Quality, Product Quality, Aesthetic Place, Customer Experience, Social Media Engagement, and Digital Brand Equity. Data were collected through a survey of 157 respondents who are customers of Kopi Menakar. Data analysis was conducted using multiple regression to determine the effect of each independent variable on the dependent variable, namely consumer purchase decisions. The results of the study indicate that all independent variables have a significant effect on consumer purchase decisions. Aesthetic Place has the greatest influence, followed by Customer Experience, Product Quality, Service Quality, and Social Media Engagement. The coefficient of determination (R²) value of 0.667 indicates that 66.7% of the variability in purchase decisions can be explained by the independent variables in this model. This study suggests that Kopi Menakar should focus on improving service quality, product quality, and customer experience to enhance consumer purchase decisions. Additionally, special attention should be given to the design and aesthetics of the place as well as social media engagement. The limitations of this study include limited generalization of the results and not considering other variables that might influence purchase decisions. These findings provide valuable insights for the management of Kopi Menakar and other coffee shop businesses in designing effective marketing strategies to enhance customer satisfaction and loyalty